Using joint control to teach activities of daily living and vocational tasks to students with autism. (6th December 2021) - Hozella, Willow; Garcia, Yors A.; Ackerlund Brandt, Julie A.; Mahoney, Amanda
Abstract: The purpose of this study was to assess the efficacy of a self‐rehearsal procedure to teach five individuals with autism to follow multiple‐step selection of stimuli. Within a multiple probe design across participants, participants were taught to echo the experimenter's instruction, self‐echo, and then select multiple pictorial stimuli in order from an array of directly trained and untrained sets of stimuli. Self‐rehearsal and selection related to activities of daily living in the natural environment required direct training. Probes of novel multiple‐step tasks were conducted. Implications for the role of joint control in developing skills sequences to teach generative responding, conceptual analyses of covert verbal behavior, and designing instructional goals related to transition from formal education settings are discussed.